CONFLICT BETWEEN TRADITION AND RELIGION: A SOCIOLOGICAL REPRESENTATION OF HASNAN SINGODIMAYAN'S NOVELS - Heru S.P. Saputra; Sunarti Mustamar; Abu Bakar R.M.; Zahratul Umniyyah (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Hasnan Singodimayan's novels express many sociological reflections on the condition of the Using community, Banyuwangi, especially regarding the conflict between tradition and religion. This study aims to examine Hasnan Singodimayan's novels to understand the ideology contained in these works. The research uses qualitative methods with a sociological approach to literature. The results showed that the author's background in the novel Kerudung Santet Gandrung sided with the traditional arts and "abangan" faced by "santri" and modern. The author's construction is different from mainstream perception by prioritizing "gandrung" dancers and local songwriters rather than santri. In contrast, the author's intention in the novel Niti Negari Bala Abangan sided with the historical and cultural values of Banyuwangi, namely Blambangan. Blambangan's identity is a representation of the Banyuwangi people's past and the Using culture. These two novels by Hasnan can be interpreted as a struggle to maintain the culture of Using.